HIV and/or AIDS awareness among adolescents in a South African at-risk rural community - Simon Taukeni; Ronel Ferreira (AOSIS, 2016)
Background: The devastating effects of HIV and/or AIDS are widely documented. Despite ongoing efforts to address the challenges associated with the pandemic, the impact on children orphaned because of the disease, as well as on adolescents, remains problematic. More specifically, orphaned adolescents living in poverty are particularly vulnerable and are often exposed to, for example, emotional and physical abuse and transactional sexual exploitation. Against this background, the importance of informed awareness among adolescents is continually emphasised, yet the outcomes of awareness campaigns require ongoing research. Objectives: The main objective of this study was to explore HIV and/or AIDS awareness among adolescents living in a rural community in South Africa, in the Chris Hani District of the Eastern Cape Province. Sixteen adolescents (aged 12-24) who had lost one or both of their parents because of HIV and/or AIDS-related reasons were purposefully selected to participate in the study. Method: For this qualitative investigation, we implemented a descriptive case study design. Semi-structured individual interviews, observation and field notes were used to collect and document data, and inductive thematic analysis was completed using the software programme Atlas.ti 7. Results: The three themes that were identified relate to HIV and/or AIDS awareness, disclosure of parents' HIV and/or AIDS status and experiences of adolescents surrounding the death of their parents. Adolescents of the community viewed HIV and/or AIDS as an infectious disease that can lead to death; however, this can be prevented by avoiding at-risk sexual behaviour. Schools and family members were the main sources of information regarding HIV and/or AIDS to the participants. Even though parents tended not to disclose their HIV and/or AIDS status, adolescents became aware of their parents' status when reading about this on their parents' medical report cards or when being told about the status by others following the death of their parents. For adolescents, their parents' deaths were associated with the parents being chronically ill or showing visible signs of deterioration such as weight loss. Conclusion: The study concludes that even though current campaigns and informative interventions have seemingly succeeded in ensuring HIV and/or AIDS awareness among adolescents - also those in remote areas - continued educational campaigns are important. Such initiatives may prove to be beneficial by focusing on ways that parents can discuss HIV and/or AIDS-related issues with their children and disclose an HIV-positive status.